Surface plasmon resonance spectroscopy study of electrostatically adsorbed layers - Gandubert, Valérie J (Langmuir : the ACS journal of surfaces and colloids, 2006)
The use of 4-(dimethylamino)pyridine to form an adhesion layer for the adsorption of anionic polyelectrolytes on gold surfaces is investigated. In situ surface plasmon resonance spectroscopy is used to monitor the changes in thickness of the adsorbed layers as a function of pH changes. Weak (poly(acrylate)) and strong (poly(styrenesulfonate)) polyelectrolytes have been studied. Although 4-(dimethylamino)pyridine is weakly bound to gold, it is not displaced by these polyelectrolytes and acts as an adhesion layer. The relationship of the interaction of anionic polyelectrolytes with 4-(dimethylamino)pyridine-modified planar gold and gold nanoparticles is discussed